Narrating Conservatism: Islamic Discourse and Its Role in Shaping Social and Educational Values in Indonesia - Syafruddin Syafruddin; Syamsul Arifin; Husnatul Mahmudah (International Journal of Educational Narratives, 2026)
Background. The increasing visibility of conservative Islamic expressions in Indonesia reflects broader socio-religious transformations shaped by globalization, democratization, and digital media expansion. Rather than a purely ideological shift, this phenomenon involves the construction and circulation of religious narratives that influence social and educational values. Purpose. This study aims to examine how conservative Islamic narratives are constructed and to analyze their roles and impacts within social and educational contexts in Indonesia. Method. This study employs a qualitative approach using a systematic literature review. Relevant academic sources were critically analyzed through a thematic synthesis, integrating perspectives from critical discourse analysis and social construction theory to explore how religious meanings are produced, disseminated, and internalized. Results. The findings reveal that conservative Islamic narratives are constructed through key discursive strategies, including textual literalism, moral polarization, and the reinforcement of religious authority. These narratives contribute to moral formation, identity consolidation, and social cohesion, but may also generate exclusivism, reduced dialogical engagement, and social polarization, particularly in digitally mediated environments. Conclusion. The study concludes that Islamic conservatism should be understood as a dynamic and contested narrative process. Religious moderation (wasathiyah) is proposed as a strategic counter-narrative that promotes balance, inclusivity, and contextual interpretation, particularly within educational settings. The study also offers a conceptual model linking socio-historical drivers, narrative construction, and social-educational impacts.